2005
DOI: 10.1111/j.1525-1438.2005.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously detected primary malignant tumors of ovary and endometrium with unusual histology

Abstract: A case of a mucinous adenocarcinoma of the ovary with a synchronous endometroid tumor of the endometrium with focal features of undifferentiated carcinoma and deep myometrial invasion is reported. A review of the literature revealed that our case is interesting in view of the fact that simultaneous presentation of primary ovarian and endometrial neoplasms is rare and usually related to low-stage ovarian lesions and well-differentiated and superficial endometrial carcinomas in contrast to our case with the foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, according to the reports, the prognosis in most cases of double primary malignant tumor is surprisingly good. It is reported that the prognosis of the "highly malignant" tumor does not worsen as a result of a second malignant cancer [8] and furthermore the prognosis of double primary carcinoma of uterine corpus and ovary is rather good [9,10]. The precise mechanism of good prognosis of double primary cancer has not been revealed yet.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the reports, the prognosis in most cases of double primary malignant tumor is surprisingly good. It is reported that the prognosis of the "highly malignant" tumor does not worsen as a result of a second malignant cancer [8] and furthermore the prognosis of double primary carcinoma of uterine corpus and ovary is rather good [9,10]. The precise mechanism of good prognosis of double primary cancer has not been revealed yet.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of studies identified in this systematic review were retrospective cohort studies with <50 patients with SEOC (6-10, 12, 22, 24, 25, 28, 31, 34, 37, 38, 42, 44, 49, 51, 52, 55, 56, 58, 59, 61, 62, 65, 67-71), cases series of individual patients (13,23,35,36,43,45,66,73), and case reports (26,27,32,33,41,46,50,53,54,57,60,63,64,72,74,75). As expected, the heterogeneity among these studies with low numbers of patients was high.…”
Section: Immunohistochemical Stains Of An Endometrial Cancer Specimenmentioning
confidence: 99%
“…However, when both tumors share the same histological features, it may be difficult to distinguish between metastatic and independent malignancies. 14,15 For accurate differentiation of these 2 distinct cancers, several clinicopathologic criteria have been proposed. In 1985, Ulbright and Roth 9 delineated a set of pathological criteria to help distinguish metastatic disease from synchronous primary tumors.…”
Section: Discussionmentioning
confidence: 99%